2011
DOI: 10.1002/hep.24386
|View full text |Cite
|
Sign up to set email alerts
|

Long-term propagation of serum hepatitis C virus (HCV) with production of enveloped HCV particles in human HepaRG hepatocytes

Abstract: HepaRG human liver progenitor cells exhibit morphology and functionality of adult hepatocytes. We investigated the susceptibility of HepaRG hepatocytes to in vitro infection with serum-derived hepatitis C virus (HCV) particles (HCVsp) and the potential neutralizing activity of the E1E2-specific monoclonal antibody (mAb) D32.10. The infection was performed using HCVsp when the cells actively divided at day 3 postplating. HCV RNA, E1E2, and core antigens were quantified in HCV particles recovered from culture su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…An additional cell line has proven to be useful for studies of both HBV 81 and HCV 82 : the HepaRG cell line. This cell line was developed from cells obtained from a resection of tumour from an HCV-infected individual with liver cancer, although the infection was not sustained in vitro after isolation of these cells.…”
Section: Hepatoma Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional cell line has proven to be useful for studies of both HBV 81 and HCV 82 : the HepaRG cell line. This cell line was developed from cells obtained from a resection of tumour from an HCV-infected individual with liver cancer, although the infection was not sustained in vitro after isolation of these cells.…”
Section: Hepatoma Cell Linesmentioning
confidence: 99%
“…Unfortunately, the use of polyethylene glycol is needed to facilitate viral entry by increasing interactions between the HBV virion and the cell membrane but the overall infection rate is low with minimal cell-to-cell virus spread 85 . Later, investigators were able to use this cell line as a substrate for HCV infection 82 . In this study 82 , the investigators were able to utilize serum-derived HCV genotype 3 to validate susceptibility to HCV infection 55 .…”
Section: Hepatoma Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…A human liver progenitor cell line, named HepaRG, can be differentiated into hep atocytes with specific cell culture conditions and has been widely used for HBV infection experiments. It could now be shown that these cells are also susceptible to serum-derived HCV particles and support long-term production of viral particles, albeit at very low levels (Ndongo-Thiam, Berthillon et al 2011). Primary human hepatocytes (PHH) provide the closest in vitro model for the natural host cell of HCV.…”
Section: Hcv Replication Models In Primary Cells and Patient Isolatesmentioning
confidence: 99%
“…Recently, HepaRG progenitor cells were shown to be capable of differentiating into hepatocytes and biliary epithelial cells, depending on culture conditions [3]. These progenitors were used as a surrogate for primary human hepatocytes [4], and showed to be susceptible to in vitro infection with serum-derived HCV (genotype 3) and able to support long-term production of infectious lipoprotein-associated enveloped HCV particles [5]. Taking these findings a step further, the model described by Schwartz, Trehan et al offers the possibility to study genetic defects that impact HCV infection of human iPS-derived hepatocyte-like cells (iHLCs) [6].…”
mentioning
confidence: 99%